Lip pattern types among mandailing bataknese and sundanese in padang city, sumatera barat province, indonesia: Study cross-sectional - Amalia, Afifah Fitri; Nismal, Harfindo; Sari, Desy Purnama (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACT Introduction: The immigrant community from West Sumatra comes from various ethnic groups in Indonesia, including Batak Mandailing (proto-Malay) and Sundanese (deutro-Malay). West Sumatra is known as a "Disaster Supermarket" region, so antemortem data is important for individuals in determining identity, one of which is lip prints. The advantages of lip patterns include being permanent because it does not change from the age of six weeks intraurine until death,  being specific, unique and individual, and being simple and cheap to apply. This study aims to determine the dominant lip print pattern of the Mandailing and Sundanese Batak Tribes in West Sumatra based on the Suzuki and Tsuchihashi classifications. Methods: The type of research is descriptive observational study using a cross-sectional approach with survey methods. The sample consisted of 28 respondents from the Mandailing Batak tribe and 28 respondents from the Sundanese tribe. The ethnicity of the respondents was determined by the previous two descendants, aged 17–40 years, with lips that had no inflammation or abnormalities and had never had surgery. Lip prints are taken using lipstick, then printed with cellophane and analyzed using a computerized system. Next, the types of lip prints are classified based on the Suzuki and Tsuchihashi classifications. Results: The dominant lip print patterns of the Mandailing Batak tribe are type I (60,7%) and type III (28,6%); while Sundanese lip print pattern is type I (82.1%). Conclusion: The dominant lip print patterns of the Mandailing Batak and Sundanese tribe are types I (complete vertical).KEY WORDS:  pattern, lip prints, ethnicity, suzuki, and tsuchihashi, classificationPola sidik bibir suku Batak Mandailing dan Sunda di Kota Padang, sumatera barat, Indonesia berdasarkan klasifikasi suzuki dan tsuchihashi: Studi cross-sectionalABSTRAK Pendahuluan: Masyarakat pendatang Sumatera Barat berasal dari berbagai suku bangsa di Indonesia, diantaranya Batak Mandailing (proto-melayu) dan Sunda (deutro-melayu). Sumatera Barat dikenal sebagai daerah “Supermarket Bencana” sehingga data antemortem menjadi hal penting bagi individu dalam menentukan identitas, salah satunya dengan sidik bibir. Keunggulan iidentifikasi dengan sidik bibir diantaranya yaitu bersifat permanen sebab tidak berubah sejak usia 6 minggu intrauterine hingga meninggal dunia, bersifat khas, unik dan personal serta mudah dan murah untuk diaplikasika.  Tujuan penelitian ini bertujuan untuk mengetahui pola sidik bibir dominan pada Suku Batak Mandailing dan Sunda di Sumatera Barat berdasarkan klasifikasi Suzuki dan Tsuchihashi. Metode: Jenis penelitian ini merupakan deskriptif observasional menggunakan pendekatan cross sectional dengan metode survei. Sampel berjumlah 28 responden Suku Batak Mandailing dan 28 Suku Sunda. Penentuan etnis responden ditetapkan dari dua generasi sebelumnya, berusia 17-40 tahun, dengan kondisi bibir tidak mengalami inflamasi, kelainan dan tidak pernah dilakukan operasi. Pengambilan sidik bibir menggunakan lipstik, kemudian dicetak dengan selofan dan dianalisis menggunakan sistem komputerisasi. Selanjutnya tipe sidik bibir diklasifikasikan berdasarkan klasifikasi Suzuki dan Tsuchihashi. Hasil: Pola sidik bibir yang ditemukan pada Suku Batak Mandailing adalah tipe I (60,7%) dan tipe III (28,6%), Sunda tipe I (82,1%). Simpulan: Pola sidik bibir berdasarkan klasifikasi Suzuki dan Tsuchihashi, paling banyak dijumpai pada Suku Batak Mandailing dan Suku Sunda di Kota Padang, Sumatera Barat adalah tipe I (vertikal lengkap).KATA KUNCI: pola, sidik bibir, suku, klasifikasi, suzuki dan tsuchihashi